Political economy and the ghosts of the past: revisiting the Spanish and Romanian transitions to democracy - Ban, Cornel; Tamames, Jorge (Historein, 2015)
Juan Linz and Alfred Stepan’s opus on democratic transition and consolidation put Spain and Romania at the extreme ends of these processes and paid little attention to the domestic and external economic constraints on the transition process. This paper interrogates these claims. It shows that in retrospect Spain looks a lot less exemplary and Romania a lot less hopeless than this iconic contribution suggested at the time. Moreover, while external economic shocks and local attempts to buffer them through social compensation shaped both transitions, Romanian governments faced balance of payments crises and international policy conditionality constraints, while their Spanish counterparts did not. This difference invites a greater appreciation of the role of political economy analyses when comparing the policy options of political elites ruling in times of democratic transition and consolidation.